2022
DOI: 10.1144/geochem2021-058
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry of porphyry-related solutes in ground and surface waters; an example from the Casino Cu–Au–Mo deposit, Yukon, Canada

Abstract: The Casino Cu-Au-Mo deposit is one of the largest and highest-grade porphyries of its kind in Canada, residing in an unglaciated region of west central Yukon. A batch of 22 stream water samples and eight groundwater samples were collected proximal to the deposit for the purpose of identifying the most diagnostic trace element and isotopic pathfinders associated with the hydrothermal mineralization, as well as establishing natural hydrogeochemical baselines for the area. Water chemistry around this deposit was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This study builds upon several recent investigations on metal­(loid) hydrogeochemistry in the Dawson Range, west-central Yukon, Canada (Figure ). ,,, The study area features discontinuous permafrost and is contained within traditional territory of Tr’ondëk Hwëch’in and Selkirk First Nation. Its physiography, geology and permafrost coverage have been described elsewhere. ,,, Briefly, permafrost covers ∼60% of land area, with thicknesses ranging from >150 m near ridgetops to <30 m in valley bottoms .…”
Section: Methodsmentioning
confidence: 99%
“…This study builds upon several recent investigations on metal­(loid) hydrogeochemistry in the Dawson Range, west-central Yukon, Canada (Figure ). ,,, The study area features discontinuous permafrost and is contained within traditional territory of Tr’ondëk Hwëch’in and Selkirk First Nation. Its physiography, geology and permafrost coverage have been described elsewhere. ,,, Briefly, permafrost covers ∼60% of land area, with thicknesses ranging from >150 m near ridgetops to <30 m in valley bottoms .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to Snrich hematite, they recovered ferberite, hübnerite, bismuthinite, daubréeite, tetradymite, and goethite from the sample. The geochemistry of stream and groundwaters sampled in 2017 as part of the Geological Survey of Canada (GSC) study at Casino are reported in Kidder et al (2022).…”
Section: Surficial Geologymentioning
confidence: 99%